(untitled) - Khasnabish, Bhumip (Hoboken, N.J., 2003)
Public and private networks will eventually be configured in such a way that all voice calls are routed using Internet protocols. Reviews existing and emerging standards for voice over IP. Provides detailed guidance on how to engineer an efficient VoIP network. Discusses quality of service (QoS) enforcement techniques. Shows how to prototype and test a network's performance.
Keywords: Internet telephony,Điện thoại Internet